2019
DOI: 10.1186/s43008-019-0002-x
|View full text |Cite
|
Sign up to set email alerts
|

A multigene phylogeny toward a new phylogenetic classification of Leotiomycetes

Abstract: Fungi in the class Leotiomycetes are ecologically diverse, including mycorrhizas, endophytes of roots and leaves, plant pathogens, aquatic and aero-aquatic hyphomycetes, mammalian pathogens, and saprobes. These fungi are commonly detected in cultures from diseased tissue and from environmental DNA extracts. The identification of specimens from such character-poor samples increasingly relies on DNA sequencing. However, the current classification of Leotiomycetes is still largely based on morphologically defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
226
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(245 citation statements)
references
References 106 publications
18
226
1
Order By: Relevance
“…The family level phylogenetic relationships resolved in this study are in line with the results from previous studies (85-87). Within the Leotiomycetes, all clades identified by Johnston and colleagues (88) and were represented here, are recovered. The family containing Tetracladium , Vandijckellaceae (88, 89), was included in an analysis based on 15 concatenated sequences (88).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The family level phylogenetic relationships resolved in this study are in line with the results from previous studies (85-87). Within the Leotiomycetes, all clades identified by Johnston and colleagues (88) and were represented here, are recovered. The family containing Tetracladium , Vandijckellaceae (88, 89), was included in an analysis based on 15 concatenated sequences (88).…”
Section: Discussionsupporting
confidence: 57%
“…Within the Leotiomycetes, all clades identified by Johnston and colleagues (88) and were represented here, are recovered. The family containing Tetracladium , Vandijckellaceae (88, 89), was included in an analysis based on 15 concatenated sequences (88). The tree herein differs from that result in the branching order of the Vandijckellaceae and helotioid taxa.…”
Section: Discussionsupporting
confidence: 57%
“…Myriodiscus is supported in the clade with Tympanis, but also related to Collophorina as a sister clade (Figure 2, clade J). Although our phylogeny did not yield good support in the backbone of the tree (relationships at order level in Leotiomycetes) since we used only two genes, the 15-gene phylogeny of Johnston et al (2019) shows the same relationships found here with high support for the internal nodes of the tree and will place Tympanidaceae as a family in Leotiales (Johnston et al, 2019) rather than Phacidiales (Baral, 2016;Wijayawardene et al, , 2018. Sanoamuang et al (2013) did not realize that Collophorina is a polyphyletic genus (Damm, Fourie, & Crous, 2010).…”
Section: Discussionmentioning
confidence: 74%
“…Species of the genus Cadophora (Ploettnerulaceae, Helotiales, Leotiomycetes) are frequently associated with living plant roots and classified as so-called dark septate endophytes (DSEs), a polyphyletic group of non-pathogenic, root-colonizing fungi characterized by melanized hyphae conspicuous when observing roots under the microscope (Jumpponen 2001;Sieber 2002;Addy et al 2005). Cadophora has close phylogenetic affinities with other helotialean lineages with well-known root-associated habits, such as Leptodontidium, Acephala, or Phialocephala (with its teleomorph in Mollisia)-constituting the 'mollisioid clade' sensu Johnston et al (2019)-and more distantly with mycorrhizal fungi in the Hyaloscyphaceae (Johnston et al 2019). Whereas Cadophora species are also common as plant pathogens and colonizing substrata other than roots, such as wood or soil (Lagerberg et al 1927;Bills 2004, p. 2;Gramaje et al 2011;Crous et al 2017), several lines of evidence suggest a degree of adaptation in the genus toward a symbiotic association with plant roots or, leastwise, the possession of a genomic toolbox favoring the evolution of such a lifestyle.…”
Section: Introductionmentioning
confidence: 99%